727 Pulmonary Embolism Following Posterior Shoulder Dislocation and Traumatic Brachial Plexus Injury - a Case Report. (19th August 2022) - Noton, T; Khanom, S; Abd Wahab, EH; Gerakopoulos, E; Colegate-Stone, T
Abstract: Traumatic brachial plexus injuries are considered to be among the rarest but most debilitating complications of shoulder dislocation. In addition, posterior shoulder dislocations are also rare, accounting for only 2–4% of all shoulder dislocations. A 40-year-old female patient presented to the emergency department (ED) with a dislocated right shoulder secondary to a mechanical fall. Plain film X-rays demonstrated a posterior dislocation of the humeral head. The shoulder was reduced under procedural sedation. Clinical examination after relocation demonstrated dense flaccid paralysis affecting all dermatomes and myotomes throughout the right upper limb. Urgent magnetic resonance imaging (MRI) of the shoulder showed oedematous thickening and haematoma along the brachial plexus, a large 'reverse' Hill-Sachs lesion, greater tuberosity avulsion fracture and glenohumeral capsular tear. The patient was referred to the specialist peripheral nerve injury unit, who advised nerve conduction studies and a magnetic resonance angiogram (MRA) to rule out expanding haematoma. The MRA scan revealed brachial plexus findings consistent with the MRI scan, no active bleeding, however a thrombus in the brachial vein. Two days after the MRA scan, the patient presented to ED with ongoing flaccid paralysis, severe neuropathic pain, and right-sided chest pain. Blood tests revealed a d-dimer >1000. CT pulmonary angiography confirmed extensive bilateral pulmonary emboli and she was commenced on appropriate anticoagulation. Association between brachial plexus injury, flaccid paralysis and venous thromboembolism are rare sequelae resulting from posterior shoulder dislocation. Further studies are required to investigate its incidence and establish whether all patients should receive VTE prophylaxis as standard.